Clinical characteristics and risk factors of hospital mortality in elderly patients with community-acquired pneumonia - Li, Shasha; Li, Lu; Wang, Shengyu; Wu, Hao (Frontiers in Medicine, 2025)
BackgroundCommunity-acquired pneumonia (CAP) leads to high morbidity and mortality among the elderly, with 3 million deaths annually worldwide. Multiple comorbidities significantly increase the risk. This study aims to identify independent risk factors for mortality in elderly patients with CAP to optimize individualized treatment strategies.MethodsThis single-center retrospective study was conducted at First Affiliated Hospital of Xi’an Medical University. Clinical data from elderly patients diagnosed with CAP between December 2018 and December 2023 were retrospectively collected. Logistic regression analysis was used to determine risk factors for in-hospital mortality. A nomogram was constructed based on the final model for risk assessment.ResultsA total of 613 eligible patients were included, with 68.2% being male, and a median age of 78 (IQR 70–86) years. The prevalence of hypertension, coronary heart disease (CHD), stroke, diabetes, malignancy, and chronic obstructive pulmonary disease (COPD) was 55.5, 39.8, 29.5, 27, 16.6, and 7%, respectively. The in-hospital mortality rate was 48%. Compared to survivors, non-survivors were older, had a higher proportion of males, faster heart rates, and higher rates of comorbidities. Multivariate logistic regression analysis identified age (OR 1.05, 95% CI [1.02–1.07], P < 0.01), BMI (OR 0.92, 95% CI [0.86–0.98], P < 0.01), stroke (OR 2.21, 95% [1.43–3.42], P < 0.01), ARDS (OR 4.0, 95% CI [2.17–7.37], P < 0.01), AKI (OR 2.98, 95% CI [1.77–5.01], P < 0.01), malignancy (OR 2.11, 95% CI [1.22–3.65], P < 0.01), elevated WBC (OR 1.20, 95% [1.14–1.27], P < 0.01), PLT (OR 0.995, 95% CI [0.993–0.998], P < 0.01), and albumin (OR 0.93, 95% CI [0.90–0.97], P < 0.01) as independent risk factors for in-hospital mortality. The area under the curve (AUC) of the multivariable model was 0.85 (95% CI [0.81–0.87], P < 0.01).ConclusionElderly CAP patients have a high prevalence of comorbidities and a high in-hospital mortality rate. Advanced age, low BMI, stroke, ARDS, AKI, malignancy, elevated WBC, decreased PLT, and low albumin were independent risk factors for in-hospital mortality.